Are there any agricultural effects on the capture rates of male euglossine bees (Apidae: Euglossini)? - Juan Carlos Sandino (Revista de Biología Tropical, 2004)
During 30 days male euglossine bees were bait-sampled at 12 sites, in the central Pacific coast of Colombia (ten days and four sites at each of three adjacent habitats: farmlands, highly disturbed forest and less disturbed forest) and 487 individuals were captured. Most captured individuals belonged to six species, five widely distributed through the American tropics and an endemic species. Two of the frequently captured species presented no different abundances between habitats, while the other four (67.97% of all the captured individuals), all of them big sized or long-tongued, were more frequently captured at the farmlands. A cluster analysis of the data matrix for the 23 captured species and the 12 sampling sites, grouped together the farmland sites, apart from the forest sites. It is proposed that male euglossine bees from generalist, long-tongued or big sized species, forage frequently at the farmlands, where fragrance or nectar resources may be clumped, less diverse, and present an access restricted by deep corollas or by microclimatic conditions of high temperature and low humidity